Snitching and the code of the street - Rosenfeld, Richard (The British journal of criminology, 2003)
Drawing from interviews with 20 active street offenders, we explore the social meaning and consequences of snitching (the exchange of incriminating information for reward or leniency). The snitch violates the code of the street and is universally despised by street criminals. Although few of our respondents reported that they had or would provide information to the police, the interviews indicate that snitching is rampant. We found that some forms of snitching are more acceptable than others, and the most offenders resist the identity of the snitch even when they perform the role. We also found evidence that police practices may contribute to the retaliatory violence associated with snitching. We conclude that expanded legal access for street criminals may reduce reliance on informers and help contain the spread of violence